(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In a fuzzy graph , for a subset of , the representation of with respect to in terms of strength of connectedness of vertices are distinct then is called the fuzzy resolving set of . In this article, we discuss the properties of fuzzy resolving set and fuzzy resolving number. And also proved some theorems and properties of fuzzy resolving number in fuzzy cyclic and fuzzy labeling graphs.